Естетична цінність ландшафту як один із критеріїв створення об’єктів природно-заповідного фонду - Бучко, Жанна Іванівна (Рахів, 2008)
Problems of finding, evaluation, reservation and rational use of nature landscapes aesthetic value are substantiated. Proposals of reservation and rational use of aesthetic potential of mountain landscapes for tourism are offered. The main direction of use of results aesthetic evaluation of landscapes should become creation of ecotourism routes in territories with a high degree of aesthetic value.
Aesthetic value of landscape as one of criterion of the Nature Protected Fund’s sites designation
Keywords: Ландшафт; естетична цінність ландшафту; природно-заповідний фонд